Penerapan Augmented Reality untuk Informasi Denah Kampus Institut Teknologi Garut - Ayu Latifah; Eri Satria; Ari Hermawan (Institut Teknologi Garut, 2022)
There is no information showing the layout of the facilities on the Garut Institute of Technology campus. The purpose of this study is to create an Android-based application with the application of Augmented Reality which displays information on the layout of facilities virtually. The Research and Development (RnD) method with ADDIE development is used consisting of analyze, design, develop, implement and evaluate stages. Unity 3D software is used in the application development process. The results of this study describe campus facilities virtually, starting from an overview of security posts, parking, front office rooms, lecture classes, libraries, laboratories, halls, service rooms. Users can see real facilities with the help of virtual robots and background music in exploring each location. The results of application satisfaction testing from users show very good acceptance. Future research is expected to add a location search feature and reduce the file size of the resulting application.